2009 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2009
DOI: 10.1109/iembs.2009.5333793
|View full text |Cite
|
Sign up to set email alerts
|

A biomimetic adaptive algorithm and low-power architecture for implantable neural decoders

Abstract: Abstract-Algorithmically and energetically efficient computational architectures that operate in real time are essential for clinically useful neural prosthetic devices. Such devices decode raw neural data to obtain direct control signals for external devices. They can also perform data compression and vastly reduce the bandwidth and consequently power expended in wireless transmission of raw data from implantable brain-machine interfaces. We describe a biomimetic algorithm and micropower analog circuit archit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Developing a switching device operating in the mV range, rather than the 1 V range of current transistors, would allow (1 V/1 mV) 2 = 10 6 fold reduction in power consumption (Yablonovitch, 2008). Electronic circuits constructed using analog techniques (Sarpeshkar, 1998), which sometimes rely on bio-inspired computational architectures, show promise for reducing energy costs by up to five orders of magnitude (Sarpeshkar, 1998; Mandal and Sarpeshkar, 2007; Rapoport et al, 2009), depending on the nature of the computation and the required level of precision.…”
Section: Evaluation Of Modalitiesmentioning
confidence: 99%
“…Developing a switching device operating in the mV range, rather than the 1 V range of current transistors, would allow (1 V/1 mV) 2 = 10 6 fold reduction in power consumption (Yablonovitch, 2008). Electronic circuits constructed using analog techniques (Sarpeshkar, 1998), which sometimes rely on bio-inspired computational architectures, show promise for reducing energy costs by up to five orders of magnitude (Sarpeshkar, 1998; Mandal and Sarpeshkar, 2007; Rapoport et al, 2009), depending on the nature of the computation and the required level of precision.…”
Section: Evaluation Of Modalitiesmentioning
confidence: 99%
“…Impedance-modulation radio-frequency (RF) telemetry techniques can drastically reduce implanted-unit power consumption and operate at less than even for transcutaneous data rates as high as in brain– machine interfaces. Finally, ultra-low-power analog processing techniques [13] , [16] can enable 100-channel neural decoding at micropower levels [17] , [18] and dramatically reduce the data rates needed for communication, further reducing total power consumption. The combination of these advances in energy-efficient amplification, communication, and computation implies that implanted components in brain– machine interfaces that operate with tens of microwatts of total power consumption are feasible today.…”
Section: Introductionmentioning
confidence: 99%
“…The compression ratio, power consumption, and correlation of decoder output with encoded states and trajectories are relevant measures of performance. In previous work [12] , [13] , we have shown that an implanted neural decoder can compress neural data by a factor of .…”
Section: Introductionmentioning
confidence: 99%